A Survey of Priority Livestock Diseases and Laboratory Diagnostic Needs of Animal Health Professionals and Farmers in Uganda - Vudriko, Patrick; Ekiri, Abel B.; Endacott, Isabella; Williams, Sitira; Gityamwi, Nyangi; Byaruhanga, Joseph; Alafiatayo, Ruth; Mijten, Erik; Tweyongyere, Robert; Varga, Gabriel; Cook, Alasdair J. C. (Frontiers in Veterinary Science, 2021)
Background: Despite the investments made in veterinary diagnostic laboratory service delivery in Uganda, the scope and level of utilization remains low. This study aimed to identify the priority livestock diseases for which farmers and animal health professionals require veterinary diagnostics, assess the perception and opinion of key stakeholders on vet diagnostic services and identify the factors that influence animal disease diagnostic service delivery and utilization in Uganda. Methods: A qualitative study approach involving a survey and key informant interviews was used to collect relevant data from four target stakeholder groups: animal health workers, laboratory technologists and technicians, farmers, and key informants. Results: The most commonly reported diseases and conditions for which diagnostic services were needed were hemoparasites (east coast fever, anaplasmosis, babesiosis, and trypanosomosis), viral diseases (foot and mouth disease, lumpy skin disease, rift valley fever, papillomatosis), bacteria and protozoa diseases (brucellosis, colibacillosis, anthrax, leptospirosis, paratuberculosis, coccidiosis), endoparasites (helminths), and mastitis. The most common diagnostic tests requested by clients, but labs were unable to provide included: rapid tests for contagious bovine pleuropneumonia, foot and mouth disease, Newcastle disease, acaricide analysis, culture and antimicrobial sensitivity test, serology, and complete blood count. The most frequently reported challenges to providing diagnostic services were poor or lack of relevant equipment, insufficient or lack of supplies and reagents, high cost of reagents, inadequate or lack of laboratory staff to perform tests, and inadequate training of laboratory staff. Conclusions: This study revealed that there is a need to improve provision of diagnostic test services and to develop strategies at the government, industry, and local laboratory levels to meet the diagnostic needs of clients. Findings also suggest that the education of farmers and animal health workers on the value and benefits of performing laboratory diagnostics may help contribute to increase in sample submission and subsequent demand for diagnostic services. Finally, the improvement in laboratory quality management systems through accreditation may increase the confidence of clients in laboratory results and contribute to overall strengthening of the laboratory diagnostic services in the country.